Design of an international multicentre RCT on group schema therapy for borderline personality disorder - Wetzelaer, Pim (BMC Psychiatry, 2014)
BACKGROUND: Borderline personality disorder (BPD) is a severe and highly prevalent mental disorder. Schema therapy (ST) has been found effective in the treatment of BPD and is commonly delivered through an individual format. A group format (group schema therapy, GST) has also been developed. GST has been found to speed up and amplify the treatment effects found for individual ST. Delivery in a group format may lead to improved cost-effectiveness. An important question is how GST compares to treatment as usual (TAU) and what format for delivery of schema therapy (format A; intensive group therapy only, or format B; a combination of group and individual therapy) produces the best outcomes. METHODS/DESIGN: An international, multicentre randomized controlled trial (RCT) will be conducted with a minimum of fourteen participating centres. Each centre will recruit multiple cohorts of at least sixteen patients. GST formats as well as the orders in which they are delivered to successive cohorts will be balanced. Within countries that contribute an uneven number of sites, the orders of GST formats will be balanced within a difference of one. The RCT is designed to include a minimum of 448 patients with BPD. The primary clinical outcome measure will be BPD severity. Secondary clinical outcome measures will include measures of BPD and general psychiatric symptoms, schemas and schema modes, social functioning and quality of life. Furthermore, an economic evaluation that consists of cost-effectiveness and cost-utility analyses will be performed using a societal perspective. Lastly, additional investigations will be carried out that include an assessment of the integrity of GST, a qualitative study on patients’ and therapists’ experiences with GST, and studies on variables that might influence the effectiveness of GST. DISCUSSION: This trial will compare GST to TAU for patients with BPD as well as two different formats for the delivery of GST. By combining an evaluation of clinical effectiveness, an economic evaluation and additional investigations, it will contribute to an evidence-based understanding of which treatment should be offered to patients with BPD from clinical, economic, and stakeholders’ perspectives. TRIAL REGISTRATION: Netherlands Trial Register NTR2392. Registered 25 June 2010. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-014-0319-3) contains supplementary material, which is available to authorized users.